Marginal People in Deviant Places Ethnography, Difference, and the Challenge to Scientific Racism - Irvine, Janice M. (University of Michigan Press, 2022)
Marginal People in Deviant Places revisits early- to mid-twentieth-century ethnographic studies, arguing that their focus on marginal subcultures-ranging from American hobos, to men who have sex with other men in St. Louis bathrooms, to hippies, to taxi dancers in Chicago, to elderly Jews in Venice, California-helped produce new ways of thinking about social difference more broadly in the United States. Irvine demonstrates how the social scientists who told the stories of these marginalized groups represented an early challenge to then-dominant narratives of scientific racism, prefiguring the academic fields of gender, ethnic, sexuality, and queer studies in key ways. In recounting the social histories of certain American outsiders, Irvine identifies an American paradox by which social differences are both despised and desired, and she describes the rise of an outsider capitalism that integrates difference into American society by marketing it.